Pet Ownership Patterns and Successful Aging Outcomes in Community Dwelling Older Adults - Friedmann, Erika; Gee, Nancy R.; Simonsick, Eleanor M.; Studenski, Stephanie; Resnick, Barbara; Barr, Erik; Kitner-Triolo, Melissa; Hackney, Alisha (Frontiers in Veterinary Science, 2020)
Introduction: Diminishing cognitive and physical function, worsening psychological symptoms and increased mortality risk and morbidity typically accompany aging. The aging population’s health needs will continue to increase as the proportion of the population aged >50 years increases. PO (PO) has been linked to better health outcomes in older adults, particularly those with chronic health conditions. Much of the evidence is weak; little is known about PO patterns as people age or the contribution of PO to successful aging in community dwelling older adults. This study examines PO patterns among healthy community dwelling older adults and the relationship of PO to cognition, physical function, and psychological status. Methods: Participants in the Baltimore Longitudinal Study of Aging (>50 years old, N=378) completed a battery of cognitive, physical function, and psychological testing as well as a PO questionnaire. Descriptive and non-parametric or general/generalized linear model analyses were conducted for separate outcomes. Results: Most participants (89%) had kept pets, currently 24% have pets:14% dogs, 12% cats, 3% others. The most frequent reasons for having pets included enjoyment (80%) and companionship (66%). Most owners had kept the pet they had the longest for over 10 years (70%). PO was lower in older age decades (p<0.001). Pet owners were more likely to live in single family homes, and more likely to reside with others (p =0.001) than non-owners. Many older adults who did not own pets (37%) had regular contact with them. In regression analyses controlling for age decade, regular contact with a pet (including PO) independently predicted cognitive function [verbal learning (p=0.012) and the Digital Symbol Substitution Test, (p= 0.001)]. Regular contact was not independently associated with physical function but tended to be associated with better psychological adaptation including happiness (p = 0.073) and well-being (p = 0.073). Conclusion: PO decreases with aging. This pattern of progressive decrease is similar to the general pattern of cognitive function, physical function, and psychological status decline. Regular pet contact was associated with better verbal memory independent of age. Longitudinal analysis is required to evaluate the association of PO and/or regular contact with changes in health status over time.